2010
DOI: 10.1002/smll.201001337
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright Fluorescent Mesoporous Silica Nanoparticles

Abstract: The first successful approach to synthesizing ultrabright fluorescent mesoporous silica nanoparticles is reported. Fluorescent dye is physically entrapped inside nanochannels of a silica matrix created during templated sol-gel self-assembly. The problem of dye leakage from open channels is solved by incorporation of hydrophobic groups in the silica matrix. This makes the approach compatible with virtually any dye that can withstand the synthesis. The method is demonstrated using the dye Rhodamine 6G. The obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 24 publications
(35 reference statements)
4
88
1
4
Order By: Relevance
“…[ 32 ] UFSNP were synthesized with several different organosilane coprecursors of silica, such as methyltrimethoxysilane (MTMS), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES) (see Scheme 1 ), using two different addition methods (i.e., co-condensation and sequential-grafting methods). The main variation of parameters related to the organosilanes, while other experimental The most probable diameter represents the size of the most abundant particles in the suspension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 32 ] UFSNP were synthesized with several different organosilane coprecursors of silica, such as methyltrimethoxysilane (MTMS), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES) (see Scheme 1 ), using two different addition methods (i.e., co-condensation and sequential-grafting methods). The main variation of parameters related to the organosilanes, while other experimental The most probable diameter represents the size of the most abundant particles in the suspension.…”
Section: Resultsmentioning
confidence: 99%
“…The particle size (ranging from 20 to 50 nm) and dye loading were controlled through the timing of the synthesis and the concentration of organosilanes (triethoxysilanes), which were used as coprecursors of silica. The use of triethoxysilanes as coprecursors prevents dye leakage, [ 32 ] presumably due to the presence of hydrophobic groups, which would help to prevent water from entering the particles, and hence prevent diffusion of the dye molecules out of the particles. Despite the presence of a number of hydrophobic groups on the particles' surfaces, colloidal suspensions of most nanoparticles were quite stable (as monitored for four months).…”
Section: Particle Sizesmentioning
confidence: 99%
“…They suffer from low sensitivity and their fluorescence rapidly dies under continuous excitation [7,8]. This gives the scientists and surgeons limited working time and makes archiving of results difficult for future comparison of data and quality control.…”
Section: Introductionmentioning
confidence: 98%
“…Alternatively, the dye can also be introduced immediately during the synthe sis of mesoporous silica particles [2,23,24]. The high level of fluorescence intensity is explained by a specific spatial distribution of dye molecules in the mesopores, which favors a decrease in the degree of dye dimeriza tion despite its increasing content in the pores [2,[22][23][24]. This leads to a decrease in the level of fluorescence quenching, in contrast to what is usually observed in solutions with increasing dye concentration [27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that fluorescent mesopo rous silica particles containing an encapsulated dye are photostable [1,22] and their emission intensity is sev eral orders of magnitude higher than that of polymer based particles with incorporated semiconductor quantum dots and the initial dye [22][23][24]. Dye mole cules, such as Rhodamine 6G (R6G), FITC, Fluor 647, TMR, etc., are introduced (encapsulated) into nanochannels with diameters within 2-8 nm by impregnating mesoporous silica particles in the corre sponding dye solutions [25,26].…”
Section: Introductionmentioning
confidence: 99%